« La langue bien pendue ». Pour une nouvelle traduction de Mafalda - Claire Latxague (Caravelle)
Nearly 50 years after the release of Mafalda’s first edition in France, it is worth considering whether French readers today perceive its political dimension. This paper presents some thoughts about traces of historical context and manifestations of political compromise in this classic comic strip, created by Quino and initially published in the Argentinian press between 1964 and 1973. It pays special attention to the amount of impact it created among the readers depending upon certain translations and publishing options.